Asian Admixture in European Echinococcus multilocularis Populations: New Data From Poland Comparing EmsB Microsatellite Analyses and Mitochondrial Sequencing - Umhang, Gérald; Knapp, Jenny; Wassermann, Marion; Bastid, Vanessa; Peytavin de Garam, Carine; Boué, Franck; Cencek, Tomasz; Romig, Thomas; Karamon, Jacek (Frontiers in Veterinary Science, 2021)
The cestode Echinococcus multilocularis is the causative agent of a severe zoonotic disease, alveolar echinococcosis (AE), distributed over a vast area in northern Eurasia and North America, but its impact on human health is highly uneven between different regions. One hypothetical reason may be the genetic structure of E. multilocularis which forms four distinct clades corresponding approximately to their continents of origin: Asia, Europe, North America and Mongolia. However, there are various records of genetic variants from the ‘wrong’ region. One such example, prompting this study, is the recent record of an ‘Asian’ mitochondrial haplotype in worms from foxes in Poland but at the time not confirmed by EmsB microsatellite analysis. Therefore, worms collected from foxes in Poland were examined both by EmsB analysis and sequencing of the full cox1 gene in order to allocate the samples to the European or Asian cluster. Based on EmsB analyses of 349 worms from 97 Polish red foxes, 92% of the worms clearly showed ‘European-type’ EmsB profiles, but 27 worms from seven foxes showed profiles that clustered with samples of Asian origin. According to cox1 sequences, a total of 18 worms from 8 foxes belonged to the Asian cluster of haplotypes. The two methods did not fully agree: only 13 worms from three foxes belonged to Asian clusters by both EmsB and cox1, whereas 18 worms from nine foxes belonged to different clusters, according to each marker. Cross-fertilization between worms of Asian origin and those from the European Polish population may explain these conflicting results. The presence of clearly Asian elements in the Polish E. multilocularis population could be the result of introduction of E. multilocularis with host animals (e.g. domestic dogs), or the migration of foxes. In the absence of genetic data from eastern European countries, especially those bordering Poland, it cannot be concluded whether this Asian admixture is typical for a larger area towards central/eastern Europe, or the Polish parasite population is the western extreme of a gradient where both European and Asian elements mingle. Further studies are needed on this subject, preferably using both mitochondrial sequencing and EmsB microsatellite analysis.